ANALISIS KELAYAKAN FINANSIAL USAHA BISNIS PUPUK BOKASHI PADA CV GESTY SINO ORGANIK (GS ORGANIK) DI DESA PENFUI TIMUR, KECAMATAN KUPANG TENGAH - Barnabas Malaibeka; Sondang S. P. Pudjiastuti; Paulus Un (Buletin Ilmiah Impas, 2021)
The research conducted at CV. GS Organik, located in East Penfui Village, Centre Kupang District inDecember 2019, aimed to determine the income and feasibility of the bokashi fertilizer business that CV. GS Organic was working on. The data was collected using the case study method. Data collected in the form of primary data, obtained from interviews and secondary data, obtained from related references and literatures. Income analysis was used to determine the first purpose, while the second purposewas analyzed using R/C ratio, BEP and payback period. The results showed that: 1) the amount of income obtained from bokashi fertilizer business in CV. GS Organic in 2016-2019 was as followed: income in 2016 was Rp 13.680.002 in 2017 was Rp 22.953.334, 2018 was Rp 31.521.334 and in 2019 Rp 40.636.669; 2) The bokashi fertilizer business in CV. GS Organik in 2016-2019 was profitable and reasonable to be developed, because the income obtained was sufficient and the value of R/C ratio was more than one, namely in 2016 was 1.52, 2017 was 1.62, 2018 was 1.65 and in 2019 was 1.68. The BEP value both of production level and price, namely in 2016 was 13.160 kg and the price of Rp 1.316, in 2017 was 18.523 kg and the price of Rp 1,235, in 2018 of 24.239 kg and Rp 1.212 if stated in price, and in 2019 was 29,682 kg at the production level and the price of Rp 1.187. The payback period was also relatively quick, namely 1 year and 5 months.